Estonian Health Care System: Accomplishments and Challenges - Nei, Sandra Victoria (European Scientific Journal, ESJ, 2017)
In Estonia, everyone has a constitutional right to health. After regaining independence, the country has executed thorough and successful healthcare reforms. The changes are especially noticeable at the primary level of healthcare. Using the most common models it is investigated how Estonia’s healthcare system fits into international classifications and what models best describe the healthcare system before and after reforms. It is shown that the Bismarck model, which is chosen as a prototype for the health care system in Estonia suits well in the case of the Estonian society, better than the other models would. It corresponds well to ethical and economic reality of Estonia.